2005
DOI: 10.1159/000083259
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin: Mechanisms of Action

Abstract: Botulinum toxin (BT) has been perceived as a lethal threat for many centuries. In the early 1980s, this perception completely changed when BT’s therapeutic potential suddenly became apparent. We wish to give an overview over BT’s mechanisms of action relevant for understanding its therapeutic use. BT’s molecular mode of action includes extracellular binding to glycoprotein structures on cholinergic nerve terminals and intracellular blockade of the acetylcholine secretion. BT affects the spinal stretch reflex b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
215
1
22

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 265 publications
(241 citation statements)
references
References 60 publications
3
215
1
22
Order By: Relevance
“…Botox enters into the axon terminal through vesicle internalization and cleaves synaptosomal-associated protein 25, leading to impaired exocytosis of neurotransmitters, including acetylcholine (24). Botox was injected subserosally along the greater curvature in the anterior side of the stomach (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Botox enters into the axon terminal through vesicle internalization and cleaves synaptosomal-associated protein 25, leading to impaired exocytosis of neurotransmitters, including acetylcholine (24). Botox was injected subserosally along the greater curvature in the anterior side of the stomach (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Neurotoxin action on the central nervous system (reflex inhibition) is not immediate since toxins do not cross the blood-brain barrier and are neutralized during retrograde axonal transport [7]. Apart from inhibition of acetylcholine release, it has been shown that botulinum neurotoxin also inhibits secretion of other neurotransmitters such as substance P, glutamate and noradrenaline.…”
Section: Botulinum Neurotoxins Cause Muscle Paralysis By Inhibiting Smentioning
confidence: 99%
“…Nevertheless, spinal cord neurons still receive excitatory signals from other sources, so that the innervated muscles may still twitch, though in an uncontrolled fashion which is frequently painful and prevents purposeful movements [44,45,46]. However, if a physiotherapeutic rehabilitation program is implemented immediately after stabilization, the patient may regain a substantial part of his/her previous abilities [7, 47, 48]. Therefore, a caring team should immediately intervene in the hope to prevent muscle rigidity and shortening [49].…”
Section: The Revelation Of the Swan: Clinical Exploitation Of The Musmentioning
confidence: 99%
See 2 more Smart Citations